Основные цели и задачи конституционных норм о языках в Республике Казахстан (Journal of actual problems of jurisprudence, 2019)
The author concludes that the adoption of the law, can prevent or overcome all the problems and debates that arise in connectionwith the implementation of the principles and norms of the Constitution of the languages.